Fingolimod exerts in vitro anticancer activity against hepatocellular carcinoma cell lines via YAP/TAZ suppression - Du Jiamin; Qian Meijia; Yuan Tao; Zhang Bo; Chen Xueqin; An Ning; He Qiaojun; Yang Bo; Ye Song; Zhu Hong (Acta Pharmaceutica)
Hepatocellular carcinoma (HCC) remains a notably global health challenge with high mortality rates and poor prognosis. The deregulation of the Hippo signalling pathway, especially the overexpression and activation of downstream effector Yes-associated protein (YAP), has been demonstrated to result in the rapid malignant evolution of HCC. In this context, multiple efforts have been dedicated to targeting YAP for HCC therapy, but effective YAP inhibitors are still lacking. In this study, through a YAP-TEAD (8×GTIIC) luciferase reporter assay, we identified fingolimod, an immunomodulatory drug approved for the treatment of multiple sclerosis, as a novel YAP inhibitor. Fingolimod suppressed the proliferation of HCC cell lines by downregulating the protein levels as well as the trans-activating function of YAP. Overall, our current study not only identifies fingolimod as a novel YAP-targeting in hibitor, but also indicates that this clinically-approved drug could be utilized as a potential and feasible therapeutic drug for HCC.